PREMATURE LOSS OF PRIMARY TEETH DUE TO DENTOALVEOLAR TRAUMA AND THE IMPORTANCE OF SPACE MAINTAINERS AS PREVENTIVE TREATMENT - Hernández, Carlos Ángel Salazar; Barzola, Olga Pierina Alvarez; Arauz, Carlos Ernesto Veliz; Barzola, Andrea Nathaly Alvarez (Seven Editora, 2026)
Introduction: Dentoalveolar trauma refers to injuries affecting both hard and soft tissues, caused by various social, cultural, and even socioeconomic factors. The characteristics of these traumas in children are relatively uncommon due to pediatric physiology and anatomy. Dental treatment for pediatric patients must be carefully planned based on the child’s age and the complexity of the specific case. Methods: This research employed a mixed-methods approach, as it incorporated both quantitative and qualitative data. It followed a descriptive research design with a non-probability convenience sampling method. The sample consisted of 57 eighth-level dental students from San Gregorio de Portoviejo University. A literature review was conducted using scientific articles published in databases such as PubMed, Web of Science, Latindex, and SciELO. Results: Of the 57 students surveyed, 32 were male and 25 were female. The study aimed to identify the most frequently observed type of malocclusion in their clinical practice. The results, ranked from most to least frequent based on the number of responses, were as follows: “Class I malocclusion” with 20 votes, “Class II Division 2 malocclusion” with 19 votes, “Class II Division 1 malocclusion” with [insert number] votes, and “Class III malocclusion” with 19 votes. Conclusions: Primary dentition plays a crucial role in functions such as mastication, space maintenance for permanent teeth, and stimulation of maxillary growth. DOI: https://doi.org/10.56238/sevened2025.036-158